Segamyndun í djúpum bláæðum ganglima : uppgjör frá FSA 1975-1990 - Geir Karlsson; Pedro Riba Ólafsson; Ingvar Þóroddsson; Björn Guðbjörnsson (Læknafélag Íslands, Læknafélag Reykjavíkur, 2008)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn View/Open Objective: To evaluate the incidence of deep vein thrombosis (DVT) in a rural area of Iceland and the prevalence of post thrombotic syndrome (PTS) in patients with history of DVT. Material and methods: A retrospective study where all phlebographies (n=177) performed at the department of radiology, Akureyri Hospital, during the period 1975-1990 were re-evaluated. Information on patients with DVT (n=32) were taken both from the Hospital and the Health Center records. All patients alive in December 1997 (n=17), 10.5 years after the diagnosis of DVT were interviewed concerning PTS. Results: The incidence of DVT during the period 1975-1990 was 1/10,000 inhabitants/year, but was 2.3/10,000/ year for the period 1986-1996. The mean age was 60 years and 62% of the patients were males. In 37.5% cases DVT was localized below the popliteal vein, in another 34.4% below the inguinal ligament and 28.1% of the thrombosis extended to the pelvic vein system. Of the patients 23.3% had a history of malignancy and 20% had undergone a major operation or had trauma. Of the patients 46.7% were smokers. At 10.5 years follow-up, 71% of the patients had some problems due to PTS, and these symptoms influenced significantly their quality of daily life. Conclusions: The prevalence of DVT in Iceland seems to be only half of what foreign studies suggest and patients with history of DVT suffer frequently from PTS 10 years after the DVT. These data indicate that it is necessary to improve the long term treatment of patients with history of DVT. Tilgangur: Að kanna tíðni segamyndunar í djúpum bláæðum ganglima (deep vein thrombosis, DVT), staðsetningu þeirra og langtímahorfur þessa sjúklingahóps með tilliti til eftirsegakvilla (post thrombotic syndrome, PTS). Efniviður og aðferðir: Rannsóknin var afturskyggn. Farið var í dagbækur röntgendeildar Fjórðungssjúkrahússins á Akureyri (FSA) og teknar út allar skráðar bláæðamyndatökur (phlebography) frá ...